Dos desfiles à produção midiática: a representação cearense e a construção de narrativas no DFB 2018 - Miranda, Maria Isabella Sousa (2020)
Fashion, as a way to comunicate tastes, possibilities, and cultural manifestations, is the object of study to understand one of the multiple aspects of the current media behavior. Journalistic production is in a privileged position to transmit messages and spread speeches, some of which have fashion or events related to the theme as their focus. The research hereby presented seeks to analyze the narratives developed at DFB 2018, the largest multidisciplinary event in Latin America, which takes place annually in Fortaleza - Ceará, and how they were transposed into journalistic articles. In order for this analysis to be possible, three main fashion shows of the event were selected, taking into account the criteria of relevance and number of insertions in the national media. As a theoretical apparatus, we take into account the concepts of fashion journalism by authors like Jofilly (1991) and Caldas (1999), consumer society for authors like Bauman (2007) and Hellman (2009) and representation for Moscovici (1978) and Hall (2016). In addition, theorists like Lipovetsky (1989; 2007) and Baudrillard (1991) helped to understand the current fashion as a symbolic instance in the manifestation of the individuality. Through the Critical Narrative Analysis of the author Luiz Gonzaga Motta (2016), the fashion shows and productions of national journalists who participated in the event were analyzed, focusing on the selected corpus. We identified how the valorization of local signs, the emphasis on regional difference with other fashion producers and the thematic focus were the main strategies for the construction of narratives in these communicational processes. Keywords: DFB Festival; media representation; consumption; narratives